Analisis Kesiapan Guru Madrasah dalam Insersi Kurikulum Cinta - Qathrun Nada, Zilfania; Listiana, Heni (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Character-based education is crucial in shaping a generation that is not only academically intelligent but also possesses strong moral values. One approach applied at MI Nururrahmah is the Kurikulum Cinta, which aims to instill values such as love, empathy, tolerance, and justice. Although this curriculum has been implemented, there are various obstacles and challenges in the process. This study aims to analyze the implementation of Kurikulum Cinta at MI Nururrahmah, including the obstacles faced, the potential available, and the support needed to optimize its implementation. This research uses a descriptive qualitative approach with data triangulation techniques through interviews, observations, documentation, and questionnaires distributed to the teachers of MI Nururrahmah. The data obtained is analyzed to identify the barriers, potential, and support in the implementation of Kurikulum Cinta. The results show that although Kurikulum Cinta has been well implemented, there are some obstacles, such as egoistic attitudes in some students and limitations in time and learning facilities. However, support from the head of the madrasah and active involvement of parents provide great potential to strengthen the implementation of this curriculum. Teacher training programs also play an important role in improving the quality of value-based teaching. Kurikulum Cinta at MI Nururrahmah has shown positive results in shaping students' character, despite some challenges in its implementation. More varied strategies, increased support from parents and the head of the madrasah, as well as improvements in facilities and teacher training, are needed to maximize the implementation of this curriculum.